Parasitological research in the molecular age. Issue 11 (18th June 2019) - Selbach, Christian; Jorge, Fátima; Dowle, Eddy; Bennett, Jerusha; Chai, Xuhong; Doherty, Jean-François; Eriksson, Alan; Filion, Antoine; Hay, Eleanor; Herbison, Ryan; Lindner, Jocelyn; Park, Eunji; et al.
Abstract: New technological methods, such as rapidly developing molecular approaches, often provide new tools for scientific advances. However, these new tools are often not utilized equally across different research areas, possibly leading to disparities in progress between these areas. Here, we use empirical evidence from the scientific literature to test for potential discrepancies in the use of genetic tools to study parasitic vs non-parasitic organisms across three distinguishable molecular periods, the allozyme, nucleotide and genomics periods. Publications on parasites constitute only a fraction (<5%) of the total research output across all molecular periods and are dominated by medically relevant parasites (especially protists), particularly during the early phase of each period. Our analysis suggests an increasing complexity of topics and research questions being addressed with the development of more sophisticated molecular tools, with the research focus between the periods shifting from predominantly species discovery to broader theory-focused questions. We conclude that both new and older molecular methods offer powerful tools for research on parasites, including their diverse roles in ecosystems and their relevance as human pathogens. While older methods, such as barcoding approaches, will continue to feature in the molecular toolbox of parasitologists for years to come, we encourage parasitologists to be more responsive to new approaches that provide the tools to address broader questions.